PENGARUH PERSONALITY TRAITS DAN HEDONIC CONSUMPTION TERHADAP IMPULSIVE BUYING YANG DIMEDIASI OLEH POSITIVE FEELING DI MATAHARI DEPARTMENT STORE KOTA BANDA ACEH - Vidya Larisa; Farid Farid (Departemen Manajemen, 2021)
Mass value addition of shopping centers in several areas is often being the caused of the formation of consumer decisions to buy goods that are not planned and are not needed. This behavior is often known as impulsive buying. This impulsive buying behavior often occurs in modern shopping centers. In the Banda Aceh region as the capital of Aceh Province, there is also a phenomenon of changing consumer spending patterns. One of the enterprise in the retail industry chosen in this study is Matahari Department Store. The grounds of this study is to estimate the impact of personality traits and hedonic consumption on impulsive buying with positive feeling as a mediating variable for Matahari Department Store consumers. This study took samples of 105 respondents who were the consumers of Matahari Department Store Banda Aceh. Systematics on data collection in this research using a questionnaire method. Purposive sampling chosen as the sampling method used in this study. Hierarchical Linear Modeling (HLM) chosen as a model analysis to establish whether there is an influence from any of that existing variables. The output of the HLM analysis represent the conclusion that personality traits and hedonic consumption have an influence on impulsive buying, personality traits and hedonic consumption also affect positive feelings, positive feelings also have an impact on impulsive buying, and positive feelings partially moderate the impact of personality traits on impulsive buying. and hedonic consumption on impulsive buying.